Extratos padronizados para o tratamento de doenças crônicas: Serjania marginata Casar. (Sapindaceae) - Vieira, Silvia Cristina Heredia [UNESP] (2014)
Sapindaceae family is extensively studied on a pharmacological point of view. Serjania marginata Casar., a specie of this family, is indicated popularly for stomach aches. The objectives of this work were to standardize the chemical profile, to characterize the chemical composition of 70% EtOH extract from S. marginata, to quantify the marker substances for the specie, to assess the acute toxicity, neurotoxicity, anti-ulcerogenic, antiradical and mutagenic activities of the extract, to determine the total phenolic and flavonoid contents and to evaluate conditions of ex situ cultivation for the specie. The studies were performed with leaves of native plants from the Cerrado and of plants grown in the Garden of Medicinal Plants from the UFGD, Dourados-MS. The highest contents were achieved by the native accesses collected during February 2011 (32.6%). During the chemical screening, it was determined that the extract was composed by flavonoids, saponins, tannins, phenols and steroids. Fifteen substances were isolated which were classified as flavonoids, tannins and saponins, and the oleanolic acid 3-O-α-L-arabinopyranosyl(1→3)-α-L-rhamnopyranosyl(1→2)[β-D-glucopyranosyl(1→4)]-α-L-arabinopyranoside and 7,5”-anhidroapigenin 8-C-α-(2,6-dideoxy-5-hydroxy-ribo-hexopyranosyl)-4'-O-β-D-glucopyranoside described for the first time in the literature. The extract here studied did not show any toxic or neurotoxic effect by acute oral dose neither presented any mutagenic potential. Significant anti-ulcer activity of the extract was evidenced when applied in different pharmacological modulations, evaluated in vivo. The extracts from leaves harvested in different growing seasons evaluated through the use of the reagent DPPH showed high antiradical activity when compared to the gallic acid and quercetin, mainly due to the presence of tannins. Plants collected after flowering showed higher amounts of phenolic compounds and, before flowering, ...